The study of the Effect of Ionospheric Variables on the Astronomical Radio Signal - Khudhur, Muhanad H.; Al-Jiboori, Monim H.; Abood, Kamal M. (Iraqi Journal of Science, 2024)
In this work, the effect of the ionospheric variables on the astronomical radio signal was studied. Florida station, for the year 2014, was selected and the actual observation data of the Jupiter signal from the Radio JOVE Data Archive was used. The Radio Jove Pro software was used to determine the number of radio emissions from Jupiter that were supposed to occur. The data of the electron density and temperatures of the ionosphere for altitudes 200-500 kilometers were taken from the International Reference Ionosphere (IRI) site, where 116 supposed events were obtained, and after applying determinants for the angle of elevation of Jupiter and the elevation of the sun, this number was reduced to 45. This work aims to focus on the role of the ionosphere in blocking the radio signal coming from Jupiter. It was found that 28 events were actually observed, while 17 events were not observed. The possibility of observing is better after sunset and depends on Jupiter's height above the horizon relative to the observer. The value of F2 peak density during the night time and along the year was about 1011 to 1012 m-3 and at a height of about 270-360 km. Approximately 82% of the observations occurred when the F2 peak density was less than 6×1011 m-3 and the height was greater than 300 km, and approximately 82% of the cases of non-observation occurred when the F2 peak density was greater than 6×1011 m-3 and the height was less than 300 km. The probability of observation is greatly affected by the relationship between the value of the electron density and its height.